A new stress-based multiaxial high-cycle fatigue damage criterion - Xin Li; Jianwei Yang; Dechen Yao (Functional Materials, 2018)
A new stress-based high-cycle fatigue damage criterion for multiaxial load cases, D = αDσβDτγ is presented. This criterion is based on a critical plane approach that the damage parameter is a function of normal stress amplitude and shear stress amplitude on critical plane of maximum shear stress range. The coefficient α, β and γ in the damage function are material parameters. Tensions with torsion test data are required to ascertain these coefficients. This criterion matches the test results well and shows accurate predictions of fatigue failure life compared to some present methods.